From lignin association to nano-/micro-particle preparation: extracting higher value of lignin. Issue 21 (7th October 2016) - Zhao, Wenwen; Simmons, Blake; Singh, Seema; Ragauskas, Arthur; Cheng, Gang
Abstract : As the most abundant source of renewable aromatic compounds on the planet, lignin is gaining growing interest in replacing petroleum-based chemicals and products. Lignin nanoparticles offer many opportunities for value-added applications of lignin. Abstract : As the most abundant source of renewable aromatic compounds on the planet, lignin is gaining growing interest in replacing petroleum-based chemicals and products. Value-added applications of lignin are also essential for the economic viability of future bio-refineries. It is however an under-utilized natural resource due to its structural heterogeneities. Lignin nanoparticles offer many opportunities for value-added applications of lignin. The solution structures of lignin were proposed as one of the key elements in controlling lignin nano-/micro-particle preparation. Fundamental understanding of solution structures of lignin aid in designing and better fabrication of lignin nanoparticles. A deeper understanding of the observed experimental results also points to the need for detailed studies of lignin in solution. This review consists of two major topics, the solution structures of lignin and lignin nano-/micro-particle preparation. Suggestions for future studies regarding these two topics were also put forward.